Oral human papilloma virus infection among dental clinic attendees in Ibadan, Nigeria - Adedayo O. Faneye; Oyeteju S. Babalola; Georgina N. Odaibo; Juwon Arotiba; Olufemi D. Olaleye (AOSIS, 2022)
Background: Human papilloma virus (HPV) is associated with a subset of oropharyngeal squamous cell carcinoma and mouth or throat warts. However, there is currently limited information about oral HPV infections in Nigeria. Objective: This study aimed to provide information on the occurrence and circulating genotypes of HPV among patients attending three (one government and two private) dental clinics in Ibadan, Nigeria. Methods: An oral swab was collected from 231 dental clinic attendees in Ibadan between January 2016 and March 2017 and tested for HPV DNA by polymerase chain reaction targeting the E6/7 genes of the virus. Results: Twenty-three of the 231 swab samples were HPV DNA positive comprising 16 mono-infections and seven co-infections in 13 males and ten females. Genotype 16 was present in ten patients, genotype 6/11 in five, Genotype 18 and genotype 33 in four each, genotype 31 in three and genotype 39 in one. Twenty-one cases were high-risk HPV genotypes, while two were low-risk. samples had co-infection and five had low risk type 6/11 either as single or as co-infection. Persons who had engaged in oral sex as well as those aged 21-30 years has significantly higher prevalence. Conclusion: This study showed that although HPV genotype 16 is the most common type among dental clinic attendees in Ibadan, other genotypes are also circulating and that oral sex is a risk factor for the infection. Therefore, introducing a multivalent HPV vaccine will reduce the risk of HPV-associated oropharyngeal carcinoma and other cancers in Nigeria.